An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Selective separation of smithsonite from calcite through fluidization roasting-induced sulfidation transformation - Yuangan Chen; Yongsheng Sun; Xiaotong Wei; Peng Gao; Yanjun Li (Minerals Engineering, 2026)

Suspension oxidative roasting for enhanced gold leaching from a quartz-rich refractory gold ore: Process optimization and microstructural evolution - Yan Song; Jianping Jin; Yanjun Li; Bing Zhao; Min Sun; Yuexin Han (Minerals Engineering, 2026)

GeoMRF: A knowledge-enhanced recommendation framework for mitigating adverse geological conditions in railway tunnel construction - Qiyu Huang; Qing Zhu; Yulin Ding; Tingchen Wu; Hongyu Wang; Haoyu Wu; Qianqian Sun; Yanjun Wang (Tunnelling and Underground Space Technology, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Fluidized oxidative roasting of carbon-bearing gold ores for gold recovery: process and mechanism - Chuanlin Sun; Jianping Jin; Shoude Guo; Yanjun Li; Xinran Zhu (Minerals Engineering, 2026)

Efficient self-magnetization roasting of siderite via CO2 introduction - Tingbo Zhou; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Stability analytical solution for the geosynthetic-reinforced pile-supported embankments based on an improved three-wedge model - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Hanyan Gu; Yanjun Qiu (Geotextiles and Geomembranes, 2026)

Experimental and numerical investigation of shear buckling behaviour of friction stir welded 6013-T6 aluminium H-shaped beams - Beibei Li; Yanjun Tong; Boshan Chen; Jingfeng Wang; Hongzhuang Yang; Yihe Guo; Bingbing Sun (Engineering Structures, 2026)

Progressive Failure Mechanism and Prediction Model of Geogrid‑Reinforced Embankments under Long‑Term Service Conditions in Xinjiang, China - Weijia Sun; Caijin Wang; Xuejun Liu; Liangfu Xie; Yanjun Li; Yan Wang; Yuelong Ha; Chuanhong Qiang; Weilin Ma; Annan Zhou; Songyu Liu (Transportation Geotechnics, 2026)

Effect of laponite treatment on liquefaction-induced tunnel uplift: Evaluation based on multiple intensity measures - Jinghua Zhang; Yong Chen; Emilio Bilotta; Yuan Xie; Yanjun Xu; Yong Yuan; Haitao Yu; Qing Sun (Transportation Geotechnics, 2026)

MEHP exposure disrupts the self-renewal and differentiation of GC-1 cells by up-regulating m6A levels, leading to reproductive damage in immature rats - Yanjun Ding; Xiazhu Zhou; Yifan Hong; Jing Chen; Haohui Tang; Binrong Sun; Chunlan Long; Lianju Shen; Shengde Wu; Yuexin Wei; Guanghui Wei (Toxicology, 2026)

Selective separation of copper and arsenic from actual copper smelting wastewater via sulfurization: a critical review in advantage, competition, parameter, and monitoring - Xiaolu Sun; Yanjun Hu; Yong Liu; Hao Jin; Ning Duan; Linhua Jiang (Journal of Environmental Chemical Engineering, 2026)

A comprehensive LMUPO research framework: Integrating outdoor urban microclimates into building performance analysis and optimization - Zhixing Li; Yi Yang; Rong Xia; Yanjun Su; Zhuoyang Sun (Building and Environment, 2026)

Two-step biosynthesis of benzyl alcohol from benzoyl-CoA within the phenylalanine-derived salicylic acid biosynthetic pathway in plants - Chao Zhang; Bao Zhu; Deli Sun; Xiaowen Wu; Zhihua Wu; Suna Zeng; Pingfei Han; Yaqi Wang; Hongyi Lv; Yanjun Zhang; Peng Huang; Wei Zhang; et al. (Molecular Plant, 2026)

Recovery of smithsonite via suspension sulfidation roasting: Evaluation of surface properties and flotation behavior - Yuangan Chen; Yongsheng Sun; Peng Gao; Yanjun Li (Minerals Engineering, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Association study on the regulation of muscle development-related genes, proteins, and metabolites in different tissues by gastrointestinal flora during various developmental stages of Liaoning cashmere goats - Yinggang Sun; Xingtang Dou; Qingyu Yuan; Ran Duan; Qiying Zhan; Taiyu Hui; Yanjun Qiao; Jiaqi Li; Wangshu Li; Yunlong Guo; Dakun Lyu; Jiaqi Ge; et al. (Food Chemistry, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Ephedplics E-I: three lignans and two benzofuran-type compounds from the roots of Ephedra sinica Stapf and their neuroprotective activity - Yunlong Dou; Bowen Zhang; Meng Li; Xiaolan Wang; Shuyan Liu; Yanjun Sun; Xiaoke Zheng; Weisheng Feng (Journal of Natural Medicines, 2026)

Glycyrrhizin-modified mung bean protein for synergistic co-encapsulation of curcumin and naringenin with enhanced stability and bioavailability - Wei Sun; Jiahe Miao; Yanjun Wei; Xianggen Wu; Chenchen Gu (Innovative Food Science & Emerging Technologies, 2026)

Climate change mitigation policy and human health: Evidence from the forest farm carbon sink projects in China - Jian Liu; Yanjun Ren; Thomas Glauben; Zhanli Sun (Environmental Impact Assessment Review, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

SIRT1 protects against UVA-induced photoaging by suppressing oxidative stress and FOXO3a acetylation in human dermal fibroblasts - Wenjuan Ma; Min Jiang; Jingtao Zhang; Wenjie Liu; Yanjun Dan; Wenjia Sun; Li Ma; Leihong Xiang; Jie Ren (Journal of Photochemistry and Photobiology B: Biology, 2026)

SEC10 suppresses KLF15-mediated transcriptional activation of JAK1 and promotes BoHV-1 replication - Wenqing Ma; Xiao Yu; Yanan Xu; Fachao Sun; Mengrui Zhao; Xinlei Wang; Yanjun Huan; Xin Yin; Hongmei Wang; Hongbin He (Veterinary Microbiology, 2026)

Nanoplastics induce SH-SY5Y cell damage through oxidative stress and disruption of amino acid metabolism - Tianyi Ma; Yuyang Liu; Jingran Sun; Yanjun Fang; Yonghui Wang; Xiaoli Li; Nan Su; Mingzhu Liu; Zunquan Zhao; Jin Wu; Jialei Bai (Toxicology, 2026)

Research on single-phase thermal-hydraulic behavior of the piping system under the influence of mechanical vibration - Xu Chen; Jianxin Shi; Yuanshao Sun; Qingpeng Zeng; Wanze Wu; Xin Zhang; Xichao Liang; Yanjun Li; Jie Yang; Xinrong Wang; Yuanwei Cao (Ocean Engineering, 2026)

Comparison of dephosphorization processes for high-phosphorus oolitic hematite based on MLA mineralogical characteristic analysis - Yusen Yu; Wenbo Li; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Fluorometric and colorimetric dual-mode detection of tert-butylhydroquinone in food samples using Mn3O4/AuNPs composite nanozyme and Cu,I-doped carbon dots - Mingzhu Liu; Xueyan He; Bo Peng; Jin Wu; Zunquan Zhao; Jialei Bai; Jingran Sun; Yanjun Fang (Food Chemistry, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Interfacial biomimetic engineering synergizing with mycelium: Constructing high-strength, water-resistant, and flame-retardant formaldehyde-free composites - Junqiang Shan; Yajuan Cao; Yanjun Chen; Yingye Shen; Tianpeng Chen; Yu Sha; Wenjun Sun; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Phosphorus Speciation and Mobility in the Dredged Sediment of an Urban Lake: The Role of Coupled Fe-S-P Dynamics and Microbial Succession - Baoquan Li; Min Zhang; Jicheng Zhong; Jiayu Qin; Haiyuan Cai; Chuanzhe Sun; Fanyan Yang; Yanjun Wu; Shanshan Liu; Hui Yang; Fen Huang (Water Research, 2026)

Study on antiviral drugs degradation by UV/NH2Cl: Combination of experiments and quantum chemical calculation - Zongyu Yan; Mian Wu; Haoran Wang; Tong Xu; Shuaishuai Xin; Qianwen Wang; Guocheng Liu; Qinghua Yan; Yanlong Sun; Chengzhi Zhou; Ya-nan Zhang; Yanjun Xin (Journal of Environmental Chemical Engineering, 2026)

Unconventional seasonal variation and mechanisms of sediment phosphorus release in an Urban lake - Baoquan Li; Suisui Zhang; Yanjun Wu; Ying Li; Min Zhang; Chuanzhe Sun; Fanyan Yang; Yuyi Wang; Shanshan Liu; Hui Yang; Fen Huang; Jicheng Zhong (Journal of Environmental Sciences, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Endothelial Cell Differentiation-Related CircRNAs Drive the Differentiation of Vascular Endothelial Cells - Yu Sun; Zhuona Yin; Yidan Huang; Yanjun Chen; Hao Yin; Yuanmei Zhang; Wen Jin (Biochemical Genetics, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Sustainable ironmaking via Hydrogen-based suspension pre-reduction of hematite: reduction mechanisms, bonding behavior, and comparison with carbon routes - Xuesong Sun; Yanjun Li; Jianwen Yu; Yize Guo; Yuexin Han (Minerals Engineering, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

Enzyme-detonated CRET nanocascade ignites endogenous chemiluminescence to empower self-sufficient photodynamic therapy and tumor-specific imaging - JiaXin Zhu; YanJun He; XiaoQian Wu; KangDi Teng; YiTeng Long; Yuan Zhang; Hui Sun; WenYuan Liu; Feng Feng; Wei Qu (Chemical Engineering Journal, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Study on the treatment of complex water hardness using electrocoagulation coupled with electrodeposition - Yanlong Sun; Hangyang Feng; Qianwei Liang; Meijuan Bian; Weifeng Kong; Xingzhi Mao; Qianwen Wang; Chengzhi Zhou; Yanjun Xin; Liguo Shen (Process Safety and Environmental Protection, 2026)

A new method for efficient recovery of boron from boron-bearing iron concentrate: low-temperature fluidized selective reduction and magnetic separation - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2026)

Comprehensive utilization of Bayan Obo polymetallic ore: A review - Qiang Zhang; Yongsheng Sun; Yuexin Han; Yanjun Li; Peng Gao (Minerals Engineering, 2026)

Long-term dynamics of water persistence and the driving mechanisms in global coastal basins - Yongqi Sun; Yanjun Tian; Yongnian Gao; Shireli Erkin (Journal of Hydrology, 2026)

Internal phosphorus loading and regulatory mechanism in China's largest urban lake: Implications for eutrophication management - Yuyi Wang; Chuanzhe Sun; Yanjun Wu; Gang Pan; Robert J.G. Mortimer; Fanyan Yang; Shuailong Wen; Suisui Zhang; Lejia Zong; Hezhong Yuan; Jianghua Yu; Jicheng Zhong (Journal of Environmental Management, 2026)

Persistent luminescent nanoparticle-based immunochromatographic assay integrated with a smartphone device for simultaneous detection of aflatoxin B1 and T-2 toxin - Aimei Zhang; Mingzhu Liu; Jingran Sun; Zunquan Zhao; Yonghui Wang; Xiaoli Li; Jin Wu; Yanjun Fang; Pingping Zhang; Jialei Bai (Food Chemistry, 2026)

The impact of storage conditions on quality and shelf life of fresh-cut jackfruit: a metabolomics perspective - Yuting Huang; Wenli Zhang; Wanqing Sun; Wenzhu Shen; Yifan Cheng; Yining Xia; Yanjun Zhang; Qiong Lin (Food Chemistry, 2026)

Optimizing O3-UV process for wastewater advanced treatment with a novel mini-fluidic experimental system to minimize energy consumption: Chemical oxidation vs. advanced oxidation - Jinyu Shi; Zhimin Qiang; Yanjun Jiang; Yanyan Huang; Zhe Sun; Mohamed Gamal El-Din; Wentao Li; Mengkai Li (Water Research, 2025)

Fungicide-enhanced differentiation and multidrug resistance of Botrytis cinerea on greenhouse tomato - Bowen Zhang; Zhenren Yang; Chenhui Wang; Yuewei Sun; Yanjun Zhao; Qingchun Huang (Pesticide Biochemistry and Physiology, 2025)

Sustainable and efficient barite recovery from low-grade tailings waste: A combined and innovative solution for resource utilization - Yuanxing Yue; Yongsheng Sun; Xiaolong Zhang; Jianping Jin; Yanjun Li (Minerals Engineering, 2025)

Thermal decomposition behavior of boron-bearing iron concentrate under nitrogen atmosphere: Kinetics, mineral phase transformation and microstructure evolution - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2025)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Enhanced COP absorption refrigeration using R-1243zf/phosphonium based ILs with compression assistance for low-grade heat - Yanjun Sun; Haiqi Zheng; Bohao Yin; Wenqiang Zhang; Jianjun Meng; Dianbo Xin; Xiaopo Wang; Maogang He (International Journal of Refrigeration, 2025)

Characterization of Limosilactobacillus fermentum with the efficient conversion of fructose to mannitol and preparation of low-sugar juice - Yanjun Tong; Di Wang; Fang Sun; Rujie Liu; Ruijin Yang (Food Chemistry, 2025)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Impact of Built Environment on Urban Vitality in Shrinking Cities: Moderating Effect of Housing Vacancy - Hui Fu; Guolei Zhou; Hongri Sun; Yu Jin; Hanchun Wu; Yanjun Liu (Chinese Geographical Science, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Chrysin enhances sunitinib sensitivity in renal cell carcinoma by inducing ferroptosis via targeting PI3K/Akt/GPX4 pathway - Zixuan Chen; Weiyuan Li; Boshen Jia; Guohuan Yin; Zongrun Sun; Yanjun Tong; Sheng Cheng; Min Liu (Toxicology and Applied Pharmacology, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

Sediment dredging effects on nitrogen and phosphorus release in a stratified reservoir: Implications for internal loading management - Yanjun Wu; Hongwei Wang; Zhu Bao; Yunchuang Li; Xiaokang Hu; Chuanzhe Sun; Fanyan Yang; Baoquan Li; Shanshan Liu; Yuyi Wang; Jicheng Zhong (Journal of Environmental Management, 2025)

Assessing the effect of composted cyclosporin A fermentation residue as organic fertilizer: Focus on soil fertility and antibiotic resistance - Dong Wang; Xiang Chen; Xiaofen Li; Qingwen Zhang; Jiaqi Hou; Yuefei Li; Beidou Xi; Zhihao Sun; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Journal of Environmental Sciences, 2025)

Has the application of agricultural green technologies achieved carbon reduction? Evidence from China - Shilong Meng; Yanjun Jiang; Hongwu Sun; Yanfei Sha; Ruiyao Ying (Clean Technologies and Environmental Policy, 2025)

Trajectory tracking control of robotic fish in offshore disturbance environments via disturbance observer-based inverse sliding mode - Juntao Sun; Yanjun Liu; Fagang Bai; Xianglei Yan; Enzhi Quan; Gang Xue (Frontiers in Marine Science, 2025)
Considering the complex offshore environment, where small robotic fish are exposed to surface disturbances from wave forces, suspended particles, and model uncertainties, as well as deep-water disturbances from bottom currents, this paper proposes an inverse sliding mode control strategy based on a disturbance observer to enhance trajectory tracking robustness. The research focuses on a tail-fin-driven bionic robotic fish. Utilizing its kinematic and dynamic models, a virtual control law based on an agent dynamics model is proposed, with the tail fin integrated as a real control input. A nonlinear disturbance observer with controllable convergence characteristics is developed to estimate and compensate for disturbances, including wave forces and model uncertainties. Additionally, a velocity error correction function is introduced to mitigate the impact of strong disturbances. Based on Lyapunov theory, an adaptive sliding mode control law is derived to ensure system stability. The control law for the caudal fin swing angle and bias is obtained by inverting the virtual control inputs, applied to the robotic fish’s accurate model. Numerical simulations show that the disturbance observer’s tracking error remains below 5%, and the trajectory tracking error is within 0.1 meters, representing only 2.2% of the robotic fish’s body length. Compared to mainstream control methods, the proposed approach significantly enhances robustness in contrast to the conventional sliding mode control with observers, and exhibits substantially smaller tracking errors, especially during trajectory transitions.

Efficient flotation of surface reconstructed hemimorphite subjected to fluidization sulfidation roasting - Yuangan Chen; Yongsheng Sun; Peng Gao; Yanjun Li (Journal of Environmental Chemical Engineering, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Liquid–Liquid Phase Separation in Hereditary Hearing Loss - Kefan Tao; Yanjun Zong; Xiaozhou Liu; Xinyu Shi; Zhengdong Zhao; Yu Sun (Neuroscience Bulletin, 2025)

Using an integrated model of the extended theory of planned behavior and the temporal self-regulation theory to explain the sugar-sweetened beverage consumption in college students - Zhiqing Hu; Rui Meng; Tongtong Sheng; Qiran Cao; Yanjun Sun; Jian Yin; Yuan He (Appetite, 2025)

Seasonal freeze-thaw CO2 sink 'midday rest' phenomenon in lakes: A case study of the largest freshwater lake in the Yellow River Basin - Yue Sun; Xiaohong Shi; Ruli Kang; Zhaoxia Yang; Shengnan Zhao; Guohua Li; Yanjun Wang; Jussi Huotari (Journal of Hydrology, 2025)

Mobilization of water-dispersible colloidal chromium and nickel in basalt-derived paddy soils: Role of Fe (hydr)oxides and organic matter - Ting Liu; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Insights to enhanced coagulation based on the control of metal forms for treating acid mine drainage: Performance and mechanisms - Kun Wu; Yanjun Jia; Dandan Song; Angzhen Li; Xue Bai; Xuan Sun; Rongle Li; Zhihua Li (Journal of Hazardous Materials, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

Hydrogen-based fluidization direct reduction of high purity iron concentrate: Experimental optimization and mechanism analysis - Tingbo Zhou; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

Optimal design of marine nuclear power deaerator based on improved particle swarm optimization algorithm - Jiarui Zhao; Yanjun Li; Xu Chen; Yuan Fu; Baozhi Sun; Yuanwei Cao; Jianxin Shi (Annals of Nuclear Energy, 2025)

Efficient configuration of high-dimensional hyperparameters in deep convolutional neural networks for classification assisted by surrogate models - Rui Zhang; Yuanyuan Zhang; Chaoli Sun; Yanjun Zhang; Zehua Dong; Xiaobing Wang (Swarm and Evolutionary Computation, 2025)

Rainfall driven nitrate transport in runoff of hilly area by combining time-series monitoring of hydrochemistry and stable isotopes - Wenbo Zheng; Shiqin Wang; Heping Sun; Yanjun Shen; Jiansheng Cao (Journal of Hydrology, 2025)

Signal-on aptasensors on paper-based platform: Application of multilayer MXene nanoquencher and stabilized luminescent carbon dots - Jincai Yang; Mingzhu Liu; Jin Wu; Tianyi Ma; Yanxuan Li; Yue Zhang; Jingran Sun; Xiaoli Li; Yanjun Fang; Yonghui Wang; Lingchao Cai; Yuan Peng; et al. (Journal of Hazardous Materials, 2025)

Production of lactic acid from corn straw: One step and two step pre-treatment strategies and bioconversion efficiency evaluation - Junqiang Shan; Yanjun Chen; Caice Liang; Tianpeng Chen; Xin Zhang; Qingguo Liu; Su Chen; Wenjun Sun; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Disruption of agr quorum sensing for enhancing biofilm formation and butanol production in Clostridium acetobutylicum - Tianpeng Chen; Yuqi Wang; Yanjun Chen; Pengpeng Yang; Wenjun Sun; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Decoding the fate of antibiotic resistance genes in soil with the application of thermally treated gentamicin mycelial residues - Dong Wang; Qingwen Zhang; Zhihao Sun; Yuefei Li; Xiaomei Xie; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Bioresource Technology Reports, 2025)

Proline improves the developmental competence of in vitro matured porcine oocytes by enhancing mitochondrial function - Yazhuo Cheng; Jiyong Shang; Xilong Jia; Yongda Zhao; Jing Liu; Yanjun Huan; Jinghe Tan; Mingju Sun (Theriogenology, 2025)

Plasma membrane-associated calcium signaling modulates zinc homeostasis in Arabidopsis - Yanjun Fang; Chuanfeng Ju; Laiba Javed; Chenyu Cao; Yuan Deng; Yaqi Gao; Xuanyi Chen; Lv Sun; Yusheng Zhao; Cun Wang (Science Bulletin, 2025)

The Roles of DMT1 in Inflammatory and Degenerative Diseases - Haigang Liu; Mi Li; Yi Deng; Yanjun Hou; Liangcai Hou; Xiong Zhang; Zehang Zheng; Fengjing Guo; Kai Sun (Molecular Neurobiology, 2025)

Maternal-offspring brain and tissue cross-talk in preeclampsia: insights from a rat model - Xiaomin Xu; Haiyin Chen; Lidan Gao; Congcong Sun; Xiaoqing Li; Yanjun Li; Wenhuan Wang; Yanyan Zheng (Metabolic Brain Disease, 2025)

A hybrid approach for island recognition by synthesizing object-oriented deep learning and pixel-based adaptive thresholding: global experiments on Sentinel-2 imagery - Senlei Hou; Yanjun Tian; Yongqi Sun; Yongnian Gao (International Journal of Remote Sensing, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

Impacts of high-methoxyl pectin on structure, composition, and rheological properties of milk fat globule emulsion - Yanjun Sun; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2025)

Engineered hydrogel platform for diabetic wound healing - Jidan Cui; Jianbin Shi; Yanjun Liu; Xianbao Shi; Jin Sun; Zhonggui He; Cong Luo; Shenwu Zhang (Chemical Engineering Journal, 2025)

Design and properties of graphene film/polymer square-wave-like composites - Yanjun Xu; Shasha Wang; Xianxian Sun; Wenbo Han; Yibin Li (Chemical Engineering Journal, 2025)

Multi-omics research reveals the genetic characteristics and acid resistance mechanism of Lactobacillus delbrueckii subsp. lactis DB-8 screening from Xizang fermented dairy - Yali Tan; Sidong Qin; Luoxi Sun; Zhixuan Wang; Xiao Li; Lingyan Liu; Hanjian Zhu; Qingyu Wang; Yanjun Cai; Mengxiang Gao (Food Bioscience, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

Hierarchical carbon-incorporated boron nitride derived from protein flocculation for efficient oxidative dehydrogenation of propane - Dong Li; Yanjun Chen; Mengyao Sun; Wenwen Ma; Zean Xie; Lian Kong; Shuchong Bai; Zhen Zhao (Chemical Engineering Journal, 2025)

Activating the green revolution: farmland transfer and agricultural green technology innovation—evidence from China - Shilong Meng; Yanjun Jiang; Shiyan Qiao; Hongwu Sun (Environment, Development and Sustainability, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Intermetallic synergy in trimetallic alloy for highly-efficient hydrogen production from ammonia decomposition - Yanjun Sun; Weihao Zeng; Yangju Yang; Qiming Wu; Chun Zou (Chemical Engineering Journal, 2024)

An Al2O3@ZnO membrane for oil-in-water emulsion separation with photocatalytic regeneration prepared via a simple deposition route - Chenggui Kuang; Yanjun Li; Donghua Liu; Yongfeng Li; Daofeng Sun; Jin Chen; Donghai Ding; Guoqing Xiao (Journal of Water Process Engineering, 2024)

Characterization of the microstructure, interfacial properties and crystallization behaviours of milk fat globule and membrane isolated from acidified bovine milk and sweet whey - Yanjun Sun; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2024)

A novel selective collector MIBATC and its performance on flotation separation of chalcopyrite from sphalerite and pyrite - Xuesong Sun; Jianwen Yu; Yanjun Li; Yuexin Han; Peng Gao (Minerals Engineering, 2024)

Variation of nitrate sources affected by precipitation with different intensities in groundwater in the piedmont plain area of alluvial-pluvial fan - Heping Sun; Wenbo Zheng; Shiqin Wang; Lin Ma; Leilei Min; Yanjun Shen (Journal of Environmental Management, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

A review of factors affecting the structure, compositions, and the techno-functionalities of bovine milk fat globule and membrane - Yanjun Sun; Yrjö H. Roos; Song Miao (Trends in Food Science & Technology, 2024)

Regrowth or smart decline? A policy response to shrinking cities based on a resilience perspective - Yu Jin; Guolei Zhou; Hongri Sun; Hui Fu; Hanchun Wu; Yanjun Liu (Sustainable Cities and Society, 2024)

Efficient industrial-current-density H2O2 production in neutral medium via external-shell boron regulation on single-atom VN4 sites - Dingding Li; Yanjun Guo; Yubo Sun; Lei Bai; Jiangwei Shi; Gang Chen; Jingbo Shi; Yijiang Liu; Chenghao Jin; Zongye Yue; Jinbo Bai; Kunyue Leng; et al. (Chemical Engineering Journal, 2024)

A yarn-based sweat-activated battery constructed with conjugated electrospun nanofiber separators as a durable and high-capacity power source in textile electronics - Yanling Zheng; Huijun Sun; Yanjun Cheng; Wenhu Gao; Chenyu Wang; Jun Ju; Min Li; Xuemei Xiang; Wei Sun; Wei Wang; Zhisong Lu; Yan Qiao (Chemical Engineering Journal, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

Design of CuS composite carbon-based Ni Al-LDH multifunctional phase change composite with electromagnetic shielding performance and heat storage capacity - Silong Wang; Zhihua Sun; Yuhao Wang; Taixin Liang; Baoguo Wang; Chunfang Fan; Yanjun Chen; Changcheng Liu; Que Huang (Chemical Engineering Journal, 2024)

Short-term forecasting for ship fuel consumption based on deep learning - Yumei Chen; Baozhi Sun; Xianwei Xie; Xiaohe Li; Yanjun Li; Yuhao Zhao (Ocean Engineering, 2024)

Construction of a pathological model of skin lesions in acute herpes zoster virus infection and its molecular mechanism - Hao Zhou; Zheng Ye; Zhao Gao; Chengxi Xi; Jinxia Yin; Yanjun Sun; Bo Sun (Mammalian Genome, 2024)

Soil pH is the Primary Factor Driving the Transformation of Plant Cuticular Wax in Saline Soils - Jianfeng Yang; Tianyu Wang; Yingpeng Sun; Yu Ni; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2024)

A review of quantification methods for light absorption enhancement of black carbon aerosol - Yao Kong; Guorui Zhi; Wenjing Jin; Yuzhe Zhang; Yi Shen; Zhengying Li; Jianzhong Sun; Yanjun Ren (Science of The Total Environment, 2024)

Probiotics and Prebiotics in Subclinical Hypothyroidism of Pregnancy with Small Intestinal Bacterial Overgrowth - Qian Ouyang; Yajuan Xu; Yanjie Ban; Jingjing Li; Yanjun Cai; Bo Wu; Yingqi Hao; Zongzong Sun; Miao Zhang; Mengqi Wang; Wentao Wang; Yinkai Zhao (Probiotics and Antimicrobial Proteins, 2024)
Evaluating efficacy of probiotics combined with prebiotics in small intestinal bacterial overgrowth (SIBO) in subclinical hypothyroidism (SCH) in the second trimester. We collected data from 78 pregnant women with SCH (SCH group) and 74 normal pregnant women (control group) in second trimester, compare the differences in high sensitivity C-reactive protein (hsCRP), result of lactulose methane-hydrogen breath test and gastrointestinal symptoms assessed by GSRS scale between two groups. In SCH group, 32 patients with SIBO were selected as intervention group. Treatment with probiotics + prebiotics for 21 days; The differences of lipid metabolism, hsCRP, thyroid function level, methane-hydrogen breath test results and GSRS scores before and after treatment were compared to evaluate the therapeutic effect. (1) The positive rate of SIBO and methane, hsCRP levels in SCH group were higher than those in control group ( P < 0.05), the total score of GSRS scale, mean score of indigestion syndrome, and constipation syndrome in SCH group were higher ( P < 0.05). (2) The mean abundance of hydrogen and methane were higher in SCH group. (3) After treatment, serum levels of thyrotropin(TSH), total cholesterol(TC), triglyceride(TG), low-density lipoprotein (LDL), and hsCRP in intervention group were decreased, and high-density lipoprotein (HDL) was increased compared with before treatment ( P < 0.05). (4) After treatment, methane positive rate, total score of GSRS scale, mean score of diarrhea syndrome, dyspepsia syndrome, and constipation syndrome were decreased ( P < 0.05). (5) The average abundance of methane and hydrogen were lower. Probiotics combined with prebiotics are effective in the treatment of SIBO in pregnant SCH patients. Clinical Trial Registration Number: ChiCTR1900026326.

Heat and carbon co-activated persulfate to regenerate gentamicin-laden activated carbon: Performance, mechanism, and safety assessment - Dong Wang; Shuaishuai Xin; Yanan Dong; Zhihao Sun; Xiaofen Li; Qianwen Wang; Guocheng Liu; Yucan Liu; Yanjun Xin (Chemosphere, 2024)

Fine-tuning bromide AIE probes for Hg2+ detection in mitochondria with wash-free staining - Tian Tan; Chuang Zhang; Ying Han; Ruijun Chu; Wenyu Xi; Xulang Chen; Jingyu Sun; Hong Huang; Yanjun Hu; Xiaohuan Huang (Journal of Hazardous Materials, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

PhenoNet: A two-stage lightweight deep learning framework for real-time wheat phenophase classification - Ruinan Zhang; Shichao Jin; Yuanhao Zhang; Jingrong Zang; Yu Wang; Qing Li; Zhuangzhuang Sun; Xiao Wang; Qin Zhou; Jian Cai; Shan Xu; Yanjun Su; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Adsorption behaviors for clathrate hydrates of CO2 with mixed gases - Ningru Sun; Yanjun Li; Nianxiang Qiu; Zhen Liu; Joseph S. Francisco; Shiyu Du (Fuel, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

Housing vacancy identification in shrinking cities based on multi-source data: A case study of Fushun city in Northeast China - Hongri Sun; Guolei Zhou; Yanjun Liu; Hui Fu; Yu Jin (Journal of Geographical Sciences, 2024)

Viscosity measurement and correlation of saturated solutions of R-290 with three lubricants - Yanjun Sun; Xingdan Wang; Shibiao Wang; Xiangzhao Meng (International Journal of Refrigeration, 2023)

Hygrothermal and energy performance assessment of a passive building wall integrating PCM and bio-based hygroscopic material - Dongxia Wu; Mourad Rahim; Wendong Li; Mohammed El Ganaoui; Rachid Bennacer; Kaiyong Hu; Huan Sun; Zhili Sun; Tonghua Zou; Yanjun Zhang (Building and Environment, 2023)

Astaxanthin enhances the development of bovine cloned embryos by inhibiting apoptosis and improving DNA methylation reprogramming of pluripotency genes - Fanglong Bi; Hongxiao Xiang; Jian Li; Jianqiang Sun; Ning Wang; Wenju Gao; Mingju Sun; Yanjun Huan (Theriogenology, 2023)

Astaxanthin protects oocyte maturation against cypermethrin-induced defects in pigs - Jianqiang Sun; Jian Li; Yaodi Wang; Jiadan Qu; Fanglong Bi; Hongxiao Xiang; Xintao Zhao; Mingju Sun; Yanjun Huan (Theriogenology, 2023)

Degradation of dimethyl phthalate by morphology controlled β-MnO2 activated peroxymonosulfate: The overlooked roles of high-valent manganese species - Yanhao Wang; Yunlong Sun; Mengchun Gao; Yanjun Xin; Guangshan Zhang; Peng Xu; Dong Ma (Journal of Hazardous Materials, 2023)

Ammonia emission characteristics and ammonia injection control from stationary source in flue gas denitrification system - Zhiping Wang; Chengyi Sun; Aijun Shi; Jing Yan; Lei Nie; Lei Chen; Peili Zhou; Yanjun Ding; Yong Yang; Xianglong Jing (Journal of Cleaner Production, 2023)

A pilot study on recovery of iron from sulfur-bearing hematite ore using hydrogen-based mineral phase transformation followed by magnetic separation - Jianwen Yu; Hao Sun; Peiyu Li; Wenjie Han; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

Synthesis of bifunctional thermal response promoters for improved high-solids enzymatic hydrolysis of corncob residues - Feiyun Li; Haohao Li; Hongming Lou; Fubao Sun; Yanjun Tang (Bioresource Technology, 2023)

Adsorption Characteristics and Mechanisms of Oxytetracycline on Nano Biochar: Effects of Environmental Conditions and Particle Aggregation - Wenqiang Jia; Xiangrui Pan; Jiaying Song; Jian Wang; Weikai Sun; Yanjun Xin; Qinghua Yan; Chengzhi Zhou; Hao Zheng; Guocheng Liu (Water, Air, & Soil Pollution, 2023)

Unsupervised deep consistency learning adaptation network for cardiac cross-modality structural segmentation - Dapeng Li; Yanjun Peng; Jindong Sun; Yanfei Guo (Medical & Biological Engineering & Computing, 2023)

Importation of a novel Indian Ocean lineage carrying E1-K211E and E2-V264A of Chikungunya Virus in Zhejiang Province, China, in 2019 - Lingxuan Su; Xiuyu Lou; Hao Yan; Zhangnv Yang; Haiyan Mao; Wenwu Yao; Yi Sun; Junhang Pan; Yanjun Zhang (Virus Genes, 2023)
The chikungunya virus (CHIKV) is widespread. In Zhejiang province, China, CHIKV infection is often associated with travelers from tropical and subtropical countries. In the present study, three CHIKV isolates from serum samples of travelers in Zhejiang province in 2019 were sequenced, and phylogenetically analyzed to study their molecular characteristics. Sequence analysis showed that the non-structural protein and the structural protein had 37 and 28 amino acid mutations, respectively; no mutation site was found at the E1-A226 residue, which could increase the adaptability of CHIKV to Aedes albopictus . All three samples carried two mutations, namely, E1-K211E and E2-V264A, which were introduced to Bangladesh around late 2015 and Thailand in early 2017. Phylogenetic analysis revealed that these three CHIKVs were Indian Ocean lineage of the East Africa/Central/South Africa genotype (ECSA) and that the MF773566 strain from Bangladesh (Australia/Bangladesh 2017) had the closest evolutionary relationship. The three CHICKs imported into Zhejiang province in 2019 belonged to the ECSA genotype and had multiple amino acid variation sites. The variation in the three samples provides a certain reference for the subsequent research on CHIKV evolution.

Path Planning of Deep-Sea Landing Vehicle Based on the Safety Energy-Dynamic Window Approach Algorithm - Zuodong Pan; Wei Guo; Hongming Sun; Yue Zhou; Yanjun Lan (Journal of Marine Science and Engineering, 2023)
To ensure the safety and energy efficiency of autonomous sampling operations for a deep-sea landing vehicle (DSLV), the Safety Energy-Dynamic Window Approach (SE-DWA) algorithm was proposed. The safety assessment sub-function formed from the warning obstacle zone and safety factor addresses the safety issue arising from the excessive range measurement error of forward-looking sonar. The trajectory comparison evaluation sub-function with the effect of reducing energy consumption achieves a reduction in path length by causing the predicted trajectory to deviate from the historical trajectory when encountering “U”-shaped obstacles. The pseudo-power evaluation sub-function with further energy consumption reduction ensures optimal linear and angular velocities by minimizing variables when encountering unknown obstacles. The simulation results demonstrate that compared with the Minimum Energy Consumption-DWA algorithm, the SE-DWA algorithm improves the minimum distance to an actual obstacle zone by 68% while reducing energy consumption by 11%. Both the SE-DWA algorithm and the Maximum Safety-DWA (MS-DWA) algorithm ensure operational safety with minimal distance to the actual obstacle zone, yet the SE-DWA algorithm achieves a 24% decrease in energy consumption. In conclusion, the path planned by the SE-DWA algorithm ensures not only safety but also energy consumption reduction during autonomous sampling operations by a DSLV in the deep sea.

Evolution of the foreland basins on either side of the Tian Shan and implications for lithospheric architecture - Chao Li; Shengli Wang; Yanjun Wang; Zhiyuan He; Chuang Sun; Hugh Sinclair; Yan Chen; Shaowen Liu; Guohui Chen; Fei Xue (Marine and Petroleum Geology, 2023)

Co-assembly of stearoylated cellulose nanocrystals and GO (or CNTs) for the construction of superhydrophobic hierarchical structure with enhanced photothermal conversion - Wei Huang; Xiangyu Tang; Wuming Fan; Qianqian Sun; Yonggui Wang; Zefang Xiao; Yanjun Xie (Carbohydrate Polymers, 2023)

Unraveling roles of the intermediate settler in a microaerobic hydrolysis sludge in situ reduction process - Zhen Zhou; Yiyue Sun; Li Fu; Yi Zuo; Yanjun Shao; Lihua Wang; Chuanting Zhou; Ying An (Bioresource Technology, 2023)

High performance and mechanism of Tl(I) removal from solution by synergetic application of nanowire γ-MnOOH@biochar and free radicals: Implications to AMD treatment - Jin Wang; Shan Yu; Yanjun Jiang; Yanyi Liu; Xinni Xiong; Jun Xiao; Mengqing Sun; Jingzi Beiyuan; Juan Liu; Gang Song (Journal of Water Process Engineering, 2023)

Novel metallic Fe recovery from copper smelting slag by the deep reduction method with renewable biochar reducing agent: Phase transformation process and Fe particle growth optimization - Bing Zhao; Xiangyan Kong; Yongsheng Sun; Yuexin Han; Yanjun Li (Process Safety and Environmental Protection, 2023)

Oil solubility effect on evaporation performance with R290 as refrigerant - Yanjun Sun; Xingdan Wang; Shibiao Wang; Xiaopo Wang (International Journal of Refrigeration, 2023)

Enlarged fins of Tibetan catfish provide new evidence of adaptation to high plateau - Liandong Yang; Ning Sun; Honghui Zeng; Ying Wang; Wenjun Chen; Zufa Ding; Yang Liu; Jing Wang; Minghui Meng; Yanjun Shen; Jingliang Kang; Xiuhui Ma; et al. (Science China Life Sciences, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Comparative study of sediment phosphorus immobilization via the addition of lanthanum-modified and thermal-modified drinking water treatment sludge - Fei Sun; Yu Chen; Liwenze He; Jingxiang Tang; Yanjun Li (Environmental Science and Pollution Research, 2023)

Structural characteristics and genetic mechanism of transfer zones in an extensional rift zone: An example from the Xihu Sag, East China Sea Basin - Yanjun Cheng; Zhiping Wu; Bin Xu; Jie Zhang; Yichen Chu; Yining Dai; Lili Xu; Wenjie Sun; Saiting Ma (Tectonophysics, 2023)

Activation of peroxymonosulfate with cobalt embedded in layered δ-MnO2 for degradation of dimethyl phthalate: Mechanisms, degradation pathway, and DFT calculation - Yanhao Wang; Yunlong Sun; Ruyun Wang; Mengchun Gao; Yanjun Xin; Guangshan Zhang; Peng Xu; Dong Ma (Journal of Hazardous Materials, 2023)

Pressure melting of pore ice in frozen rock under compression - Ting Wang; Hailiang Jia; Qiang Sun; Tuo Lu; Liyun Tang; Yanjun Shen (Cold Regions Science and Technology, 2023)

Functional characterization of three TERMINAL FLOWER 1-like genes from Platanus acerifolia - Sisi Zhang; Qin Zhou; Xingyu Yang; Jianqiang Wang; Jie Jiang; Miaomiao Sun; Yanjun Liu; Chaoren Nie; Manzhu Bao; Guofeng Liu (Plant Cell Reports, 2023)

Influence of selected gums on the foaming properties of egg white powders: Kinetics of foam formation and baking performance - Junhua Li; Jinjing Sun; Cuihua Chang; Luping Gu; Yujie Su; Jiali Zhai; Yanjun Yang (Food Hydrocolloids, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Diversified chemical profiles of cuticular wax on alpine meadow plants of the Qinghai-Tibet Plateau - Jianfeng Yang; Lucas Busta; Reinhard Jetter; Yingpeng Sun; Tianyu Wang; Wenlan Zhang; Yu Ni; Yanjun Guo (Planta, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Study Regarding the Influence of Blade Rotation Angle Deviations on the Hydraulic Pulsation Characteristics of a Mixed-Flow Pump - Yanjun Li; Danghang Sun; Fan Meng; Yunhao Zheng; Yi Zhong (Journal of Marine Science and Engineering, 2023)
Mixed-flow pumps with adjustable blades are widely used in municipal, agricultural, and hydropower applications. However, a limitation of adjustable blades is that the influence of the water pressure in the pump causes the rotation angle to deviate, which not only reduces the hydraulic efficiency of the pump and increases energy consumption, but it is also detrimental to the stable operation of the pump. To investigate the influence of blade rotation angle deviations (BRADs) on the hydraulic pulsation characteristics of a mixed-flow pump, in this study, a three-dimensional unsteady numerical simulation was adopted to analyze the effects of seven BRAD design schemes on the energy performance, pressure pulsation characteristics, and axial and radial forces in the impeller. When the rotation angle of a single blade deviated counterclockwise, the optimal hydraulic efficiency point of the mixed-flow pump moved toward larger flow rates, and vice versa. Unlike a situation with no BRADs, when there were BRADs, the central symmetry of the low-pressure area near the suction surface of the impeller blades was destroyed. BRADs led to increases in the pressure pulsation amplitudes at the inlet and outlet of the impeller. The dominant pressure pulsation frequencies near the shroud side at the inlet and outlet of the impeller were not affected by BRADs (both of them were equal to the blade frequency). However, the amplitude of the dominant pressure pulsation frequency at the impeller outlet and the radial force of the impeller both increased with increases in the absolute value of the deviation angle. Moreover, when the rotation angle of a single blade was only in the counterclockwise direction, the axial force of the impeller increased. This study can provide an engineering reference for the stability of mixed-flow pumps with BRADs.

The Mesozoic tectonic evolution of the East China Sea Basin: New insights from 3D seismic reflection data - Yanjun Cheng; Zhiping Wu; Bin Xu; Yining Dai; Yichen Chu; Jie Zhang; Mingming Chen; Saiting Ma; Wenjie Sun; Lili Xu (Tectonophysics, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)

Contribution of five major apple polyphenols in reducing peanut protein sensitization and alleviating allergencitiy of peanut by changing allergen structure - Shanfeng Sun; Tianyi Jiang; Yanjun Gu; Lu Yao; Hang Du; Jiangzuo Luo; Huilian Che (Food Research International, 2023)

Transparent, intrinsically stretchable cellulose nanofiber-mediated conductive hydrogel for strain and humidity sensing - Ziyu Bian; Yinghui Li; Hongling Sun; Mengyu Shi; Yanjun Zheng; Hu Liu; Chuntai Liu; Changyu Shen (Carbohydrate Polymers, 2023)

Unravelling the regulation mechanism of nanoflower shaped Na3V2(PO4)3 in methanol–water system for high performance sodium ion batteries - Shiqi Sun; Yanjun Chen; Qiang Bai; Zhen Tian; Que Huang; Changcheng Liu; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

MLRD-Net: 3D multiscale local cross-channel residual denoising network for MRI-based brain tumor segmentation - Xue Chen; Yanjun Peng; Yanfei Guo; Jindong Sun; Dapeng Li; Jianming Cui (Medical & Biological Engineering & Computing, 2022)

Optimization of medical waste recycling network considering disposal capacity bottlenecks under a novel coronavirus pneumonia outbreak - Xueyun Mei; Hao Hao; Yichen Sun; Xinyang Wang; Yanjun Zhou (Environmental Science and Pollution Research, 2022)

Formation and evolution of secondary particulate matter during heavy haze pollution episodes in winter in a severe cold climate region of Northeast China - Ye Hong; Junying Sun; Yanjun Ma; Yangfeng Wang; Xiaolan Li; Yunhai Zhang; Ningwei Liu; Deping Zhou (Environmental Science and Pollution Research, 2022)

Fracture Mechanical Properties of Frozen Sandstone at Different Initial Saturation Degrees - Ting Wang; Qiang Sun; Hailiang Jia; Yanjun Shen; Guoyu Li (Rock Mechanics and Rock Engineering, 2022)

Matching of Residential and Commercial Space in Shrinking Cities from the Perspective of Supply and Demand: A Case Study of Yichun City, China - Yining Zhang; Guolei Zhou; Yanjun Liu; Hui Fu; Hongri Sun (Chinese Geographical Science, 2022)

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Orexin A peptidergic system: comparative sleep behavior, morphology and population in brains between wild type and Alzheimer’s disease mice - Peng Zhao; Yaqian You; Zhe Wang; Yanjun Zhou; Gaoshang Chai; Gen Yan; Zhewu Jin; Qing Wang; Hongxu Sun (Brain Structure and Function, 2022)
Sleep disturbance is common in patients with Alzheimer’s disease (AD), and orexin A is a pivotal neurotransmitter for bidirectionally regulating the amyloid-β (Aβ) deposition of AD brain and poor sleep. In the present study, we examined the characteristic of sleep–wake architecture in APPswe/PSldE9 (APP/PS1) and Aβ-treated mice using electroencephalogram (EEG) and electromyographic (EMG) analysis. We compared the expression of orexin A, distribution, and morphology of the corresponding orexin A-positive neurons using innovative methods including three-dimensional reconstruction and brain tissue clearing between wild type (WT) and APP/PS1 mice. Results from our study demonstrated that increased wakefulness and reduced NREM sleep were seen in APP/PS1 and Aβ treated mice, while the expression of orexin A was significantly upregulated. Higher density and distribution of orexin A-positive neurons were seen in APP/PS1 mice, with a location of 1.06 mm–2.30 mm away from the anterior fontanelle compared to 1.34 mm–2.18 mm away from the anterior fontanelle in WT mice. These results suggested that the population and distribution of orexin A may play an important role in the progression of AD.

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Two new benzoic acid derivatives from endophytic fungus Aspergillus versicolor - Yanqing Ye; Yanjun Chen; Yuting Hou; Hongmei Yu; Lijun Zhu; Yanqi Sun; Min Zhou; Yijian Chen; Miao Dong (Natural Product Research, 2022)

The seasonal and spatial distribution of hydrochemical characteristics of groundwater and its controlling factors in the eastern Loess Plateau - Congjian Sun; Wei Chen; Yanjun Shen (Earth Science Informatics, 2021)

Molecular epidemiologic characteristics of hemagglutinin from five waves of avian influenza A (H7N9) virus infection, from 2013 to 2017, in Zhejiang Province, China - Yi Sun; Haiyan Mao; Xiuyu Lou; Xinying Wang; Yin Chen; Biaofeng Zhou; Yanjun Zhang (Archives of Virology, 2021)
There have been five waves of influenza A (H7N9) epidemics in Zhejiang Province between 2013 and 2017. Although the epidemiological characteristics of the five waves have been reported, the molecular genetics aspects, including the phylogeny, evolution, and mutation of hemagglutinin (HA), have not been systematically investigated. A total of 154 H7N9 samples from Zhejiang Province were collected between 2013 and 2017 and sequenced using an Ion Torrent Personal Genome Machine. The starting dates of the waves were 16 March 2013, 1 July 2013, 1 July 2014, 1 July 2015, and 1 July 2016. Single-nucleotide polymorphisms (SNPs) and amino acid mutations were counted after the HA sequences were aligned. The evolution of H7N9 matched the temporal order of the five waves, among which wave 3 played an important role. The 55 SNPs and 14 amino acid mutations with high frequency identified among the five waves revealed the dynamic occurrence of mutation in the process of viral dissemination. Wave 3 contributed greatly to the subsequent epidemic of waves 4 and 5 of H7N9. Compared with wave 1, wave 5 was characterized by more mutations, including A143V and R148K, two mutations that have been reported to weaken the immune response. In addition, some amino acid mutations were observed in wave 5 that led to more lineages. It is necessary to strengthen the surveillance of subsequent H7N9 influenza outbreaks.

The association between fine particulate matter and acute lower respiratory infections in Yancheng City, China - Jin Zhuang; Hongjian Bai; Jian Sun; Ting Zhang; Jingjing Li; Yanjun Chen; Haiyan Zhang; Qian Sun (Environmental Science and Pollution Research, 2021)

A potential new recombinant echovirus 18 strain detected in a 4-year-old child with encephalitis in China in 2019 - Yanjun Kang; Ying Hua; Mingxia Sun; Jun Qian; Pengwei Zhu (Archives of Virology, 2021)

Comprehensive evaluation of hydrological models for climate change impact assessment in the Upper Yangtze River Basin, China - Shanshan Wen; Buda Su; Yanjun Wang; Jianqing Zhai; Hemin Sun; Ziyan Chen; Jinlong Huang; Anqian Wang; Tong Jiang (Climatic Change, 2020)

mRNA and microRNA Profiles in the Amygdala Are Relevant to Susceptibility and Resilience to Psychological Stress Induced in Mice - Jinyan Sun; Yanjun Lu; Jiuyong Yang; Zhenhua Song; Wei Lu; Jin-Hui Wang (Journal of Molecular Neuroscience, 2020)

Correction to: mRNA and microRNA profiles are associated with stress susceptibility and resilience induced by psychological stress in the prefrontal cortex - Jiuyong Yang; Jinyan Sun; Yanjun Lu; Tingting An; Wei Lu; Jin-Hui Wang (Psychopharmacology, 2020)

Revision to psychopharmacology mRNA and microRNA profiles are associated with stress susceptibility and resilience induced by psychological stress in the prefrontal cortex - Jiuyong Yang; Jinyan Sun; Yanjun Lu; Tingting An; Wei Lu; Jin-Hui Wang (Psychopharmacology, 2020)

Genome-wide identification of long non-coding RNAs and circular RNAs reveal their ceRNA networks in response to cucumber green mottle mosaic virus infection in watermelon - Yuyan Sun; Huiqing Zhang; Min Fan; Yanjun He; Pingan Guo (Archives of Virology, 2020)

Permeability dynamic variation of coal under various confining pressures using LFNMR relaxation method - Peng Xia; Fangui Zeng; Xiaoxia Song; Beilei Sun; Taotao Yan; Wei Li; Yanjun Meng (Arabian Journal of Geosciences, 2020)

Influence of Pore Water (Ice) Content on the Strength and Deformability of Frozen Argillaceous Siltstone - Hailiang Jia; Fan Zi; Gengshe Yang; Guoyu Li; Yanjun Shen; Qiang Sun; Pengyu Yang (Rock Mechanics and Rock Engineering, 2020)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Effects of the configuration of a baffle–avalanche wall system on rock avalanches in Tibet Zhangmu: discrete element analysis - YuZhang Bi; SiMing He; YanJun Du; XinPo Sun; XinPo Li (Bulletin of Engineering Geology and the Environment, 2019)

Transplantation of umbilical cord–derived mesenchymal stem cells on a collagen scaffold improves ovarian function in a premature ovarian failure model of mice - Yanjun Yang; Lei Lei; Shanshan Wang; Xiaoqiang Sheng; Guijun Yan; Lu Xu; Jingyu Liu; Mengyuan Liu; Xin Zhen; Lijun Ding; Haixiang Sun (In Vitro Cellular & Developmental Biology - Animal, 2019)

Follicular helper T cell and memory B cell immunity in CHC patients - Yong Liu; Huifan Ji; Pingwei Zhao; Hongqing Yan; Yanjun Cai; Lei Yu; Xiaoli Hu; Xiguang Sun; Yanfang Jiang (Journal of Molecular Medicine, 2019)

Water-soluble ion components of PM10 during the winter-spring season in a typical polluted city in Northeast China - Ye Hong; Yanjun Ma; Junying Sun; Chaoliu Li; Yunhai Zhang; Xiaolan Li; Deping Zhou; Yangfeng Wang; Ningwei Liu (Environmental Science and Pollution Research, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Numerical analysis of effect of baffle configuration on impact force exerted from rock avalanches - YuZhang Bi; YanJun Du; SiMing He; XinPo Sun; DongPo Wang; XinPo Li; Heng Liang; Yong Wu (Landslides, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Changes in Extreme Maximum Temperature Events and Population Exposure in China under Global Warming Scenarios of 1.5 and 2.0°C: Analysis Using the Regional Climate Model COSMO-CLM - Mingjin Zhan; Xiucang Li; Hemin Sun; Jianqing Zhai; Tong Jiang; Yanjun Wang (Journal of Meteorological Research, 2018)

Quantitative evaluation of the rainfall influence on streamflow in an inland mountainous river basin within Central Asia - Congjian Sun; Yanjun Shen; Yaning Chen; Wei Chen; Weibo Liu; Yongqing Zhang (Hydrological Sciences Journal, 2018)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Physiological and anatomical responses of Phyllostachys vivax and Arundinaria fortunei (Gramineae) under salt stress - Wei Ge; Ying Zhang; Zhongyuan Sun; Juan Li; Guohua Liu; Yanjun Ma; Jian Gao (Brazilian Journal of Botany, 2017)

Structural block division for further deep research in coalbed methane development in the Gujiao area, Xishan coalfield, North China - Peng Xia; Fangui Zeng; Xiaoxia Song; Yanjun Meng; Kunjie Li; Jin Wang; Beilei Sun (Arabian Journal of Geosciences, 2016)

Complete genome sequence of a sapovirus from a child in Zhejiang, China - Xiaohong Zhou; Yi Sun; Xiaochun Shang; Jian Gao; Xueqin Zhao; Huiqun Shuai; Rui Zhang; Yanjun Zhang (Virus Genes, 2016)

Regulatory function of Arabidopsis lipid transfer protein 1 (LTP1) in ethylene response and signaling - Honglin Wang; Yue Sun; Jianhong Chang; Fangfang Zheng; Haixia Pei; Yanjun Yi; Caren Chang; Chun-Hai Dong (Plant Molecular Biology, 2016)

Multiple viral introductions: molecular characterization of influenza B virus in Wenzhou, Zhejiang, China, from 2011 to 2014 based on hemagglutinin and neuraminidase genes - Dong Chen; Xiaohong Wen; Yi Sun; Haiyan Mao; Yanjun Zhang; Yin Chen; Xinying Wang; Baochang Sun; Xin Wang; Xiaoming Zhang (Archives of Virology, 2016)

Auxin signaling is involved in iron deficiency-induced photosynthetic inhibition and shoot growth defect in rice (Oryza sativa L.) - Kaidong Liu; Runqing Yue; Changchun Yuan; Jinxiang Liu; Lei Zhang; Tao Sun; Yanjun Yang; Shuanggui Tie; Chenjia Shen (Journal of Plant Biology, 2015)

Isolation and functional characterization of seed-specific FAD2-1 promoter from cotton (Gossypium hirsutum L) - Feng Liu; YanPeng Zhao; Xiaodong Wang; Yanjun Li; Jie Sun (Journal of Plant Biochemistry and Biotechnology, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

STAT4 genetic polymorphisms association with spontaneous clearance of hepatitis B virus infection - Yanjun Lu; Yaowu Zhu; Jing Peng; Xiong Wang; Feng Wang; Ziyong Sun (Immunologic Research, 2015)

Variations of cuticular wax in mulberry trees and their effects on gas exchange and post-harvest water loss - Yu Ni; Zhengyuan Sun; Xianzhi Huang; Chuanshu Huang; Yanjun Guo (Acta Physiologiae Plantarum, 2015)

Evaluating the vegetation growing season changes in the arid region of northwestern China - Yanfang Wang; Yanjun Shen; Fubao Sun; Yaning Chen (Theoretical and Applied Climatology, 2014)

Acid-Responsive Polymeric Nanocarriers for Topical Adapalene Delivery - Chenchen Guo; Rajeshree H. Khengar; Mingjing Sun; Zheng Wang; Aiping Fan; Yanjun Zhao (Pharmaceutical Research, 2014)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

In vitro study of nano-HA/PLLA composite scaffold for rabbit BMSC differentiation under TGF-β1 induction - Weimin Zhu; Kang Chen; Wei Lu; Qifeng Sun; Liangquan Peng; Wenzhe Fen; Hao Li; Yangkan Ou; Haifeng Liu; Daping Wang; Yanjun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2014)

Antisense MMP-9 RNA inhibits malignant glioma cell growth in vitro and in vivo - Cuiyun Sun; Qian Wang; Hongxu Zhou; Shizhu Yu; Alain R. Simard; Chunsheng Kang; Yanyan Li; Yanling Kong; Tongling An; Yanjun Wen; Fudong Shi; Junwei Hao (Neuroscience Bulletin, 2013)

Identification and characterization of a novel l-arabinose isomerase from Anoxybacillus flavithermus useful in d-tagatose production - Yanjun Li; Yueming Zhu; Anjun Liu; Yuanxia Sun (Extremophiles, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)

Effect of NaCl on leaf H+-ATPase and the relevance to salt tolerance in two contrasting poplar species - Xiuying Ma; Lin Deng; Jinke Li; Xiaoyang Zhou; Niya Li; Decai Zhang; Yanjun Lu; Ruigang Wang; Jian Sun; Cunfu Lu; Xiaojiang Zheng; Eberhard Fritz; et al. (Trees, 2010)

Some large values of in-situ stress and related engineering geological problems in China - Yanjun Shang; Hyeong-Dong Park; Yongyue Shi; Guangxiang Yuan; Yuanchun Sun (Geosciences Journal, 2010)

From in situ stress and discontinuities to the strength of granites: comparison and case study - Yanjun Shang; Hyeong-Dong Park; Guangxiang Yuan; Yuanchun Sun; Qian Gao (Geosciences Journal, 2008)

Variation of fluxes of water vapor, sensible heat and carbon dioxide above winter wheat and maize canopies - Zhang Yongqiang; Shen Yanjun; Yu Qiang; Liu Changming; A. Kondoh; Tang Changyuan; Sun Hongyong; Jia Jinsheng (Journal of Geographical Sciences, 2002)